Pemberdayaan Masyarakat Desa Sukajadi Melalui Program Pendidikan, Kesehatan, Ekonomi, dan Lingkungan Berbasis Potensi Lokal - Teguh Ikhlas Ramadhan; Rendi Agustiana; Erlangga Mahardika Putra (Journal of Empowerment Community, 2026)
This community empowerment program in Sukajadi Village implemented integrated interventions across education, health, economy, and environment sectors using participatory rural appraisal methodology. Key activities included establishing Mini English Club, health education campaigns, digital marketing training for MSMEs focusing on local products (furniture and fermented cassava), and integrated waste management systems. Results showed significant achievements: 75% increase in community participation, 80% of MSMEs successfully established online business presence, functional waste bank processing 50 kg of waste weekly, and 85% of households demonstrated enhanced environmental awareness. The program effectively empowered the community by optimizing local potential while ensuring sustainability through context-specific approaches.